(untitled) (Fiep Bulletin - online, 2011)
This examination intends to verify in which measure the sociodemographic factors influence loyalty to sportive consumption in 8 Fitness centers for women in Lisbon. 489 questionnaires were picked up and the loyalty indicators were verified from consumption to physical exercise practice of Villares e Coelho (2005). Data base were treated through Statistical Package for The Social Sciences (SPSS 16.0 for Windows) program version. The socialdemographic’s analysis indicates that most practitioners belong to age group between 21 and 40 years old, existing differences along literally abilities, graphic nearness and time of fitness practice. We concluded that in this study the groups with higher loyalty were: a) lower literally ability; b) lower distance between work and home in relation to the gym; c) groups with 0 to 2 years practicing are more loyals.